An Organic Mixed‐Valence Ligand for Multistate Redox‐Active Coordination Networks. Issue 17 (13th March 2018) - Ha, Joo Yeon; Koo, Jin Young; Ohtsu, Hiroyoshi; Yakiyama, Yumi; Kim, Kimoon; Hashizume, Daisuke; Kawano, Masaki
Abstract: The multistate redox‐active/multi‐interactive ligand 5, 5′, 8, 8′‐tetra(4‐pyridyl)‐2, 2′‐(1, 4‐phenylene)bis‐1 H ‐perimidine (H2 TPP) was designed and synthesized. H2 TPP undergoes four one‐electron oxidation steps, and was used for the preparation of a multistate redox‐active coordination network in a solid–liquid interface reaction using molten Cd 2+ salts. The multiple redox states of H2 TPP were confirmed spectroscopically by stepwise four‐electron oxidation. Spectroscopic analysis indicated that the mixed‐valence states of the ligand are class II on the UV/Vis/NIR timescale and borderline class II/class III on the ESR timescale. Abstract : A redox‐active coordination network was prepared in a solvent‐free molten‐metal process with the new multistate redox‐active/multi‐interactive ligand H2 TPP. The ligand as well as the network can adopt multiple redox states, including mixed‐valence (MV) states, owing to the two redox‐active moieties in the H2 TPP ligand.